Analisis Pengaruh Kualitas Produk Dan Promosi Terhadap Impulsif Buying Pada Produk Wardah (Studi Pada Mahasiswa Universitas Putra Indonesia Cianjur) - Wenny Djuarni; Ira Mariyah Ulfah; Dhiya Nada Adilah (Jurnal Digitalisasi Akuntansi, 2025)
Purpose: This study aims to examine the effect of product quality and promotion on impulsive buying behavior of Wardah cosmetic products among students of Universitas Putra Indonesia Cianjur. The research addresses whether impulsive buying is driven more by perceived product quality or promotional strategies. Methodology/approach: A quantitative research design was employed using survey data collected through questionnaires distributed to 86 Wardah consumers selected using the Slovin formula with a 5% margin of error. Data were analyzed using validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination with SPSS. Results/findings: The findings show that product quality has a negative and significant effect on impulsive buying, while promotion has a positive and significant effect. Simultaneously, both variables significantly influence impulsive buying, with promotion identified as the dominant factor. Conclusion: The study concludes that promotional activities play a more decisive role in triggering impulsive buying behavior, whereas product quality is more associated with planned purchases. These results highlight the strategic importance of promotion in influencing spontaneous consumer decisions in the cosmetic industry.